A HIGH PREOPERATIVE NEUTROPHIL-LYMPHOCYTE RATIO AS AN INDICATOR OF EARLY RESPONSE OF KIDNEY TRANSPLANT (Indonesian Journal of Urology, 2023)
Objective: This study aims to evaluate the association of the preoperative Neutrophil-lymphocyte ratio (NLR) and postoperative creatinine levels after kidney transplantation, which is a predictor factor for determining early postoperative transplantation complications. Material & Methods: We conducted a retrospective study of 33 patients enrolled in Sardjito General Hospital in Yogyakarta between 2017 and 2020. In this study, we observed the preoperative NLR and compared it with the postoperative creatinine level. The data were compared and analyzed. Results: This study showed that preoperative NLR in these 33 patients was 4.17 + 2.82. Postoperative creatinine levels were 2.38 + 1.75 mg/dL. Postoperative creatinine levels were higher in patients with low preoperative NLR (p=0.00). Besides, the correlation is weak and had a positive correlation direction (r=0.379). Conclusion: This study showed preoperative NLR and the postoperative serum creatinine level is correlated even weakly. NLR could be considered a predictor factor for determining postoperative transplantation complications, and even it still needs further research.